Study on Soil Erosion in Yinghe River Basin Based on ArcGIS and USLE Model - SI Jiaji (Renmin Zhujiang, 2020)
Based on ArcGIS spatial analysis technology and USLE model, this paper conductsquantitative study on the soil erosion to explore the occurrence of soil erosion under differentsoil types and land use patterns in the Yinghe River basin. The results show that: The averagesoil erosion modulus of the Yinghe River Basin in 2017 was 403.3 t/(km2·a-1), and the totalamount of soil erosion is 388 781 t/a. The farmland is the main landuse pattern under soilerosion, with a total erosion area of 86.52%, followed by residential land. Four soil typeshave different degrees of soil erosion, of which the total erosion area of Shajiang black soil isthe widest, next to fluvo-aquic soil. The soil is mainly dominated by mild and light erosion,accounting for 59% and 33% of the total area of erosion.